2018
DOI: 10.1016/j.jaci.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of peanut sensitization following exposure through breast-feeding and early peanut introduction

Abstract: In this secondary analysis, maternal peanut consumption while breast-feeding paired with direct introduction of peanuts in the first year of life was associated with the lowest risk of peanut sensitization, compared with all other combinations of maternal and infant peanut consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
(38 reference statements)
2
32
0
1
Order By: Relevance
“…Interestingly enough, the lowest incidence at 1.7% was found in children whose mothers ate peanuts while breast-feeding and were introduced to peanuts before 12 months of age. If a mother did not do one of these actions, there was an increase in incidence of peanut sensitization [59]. This study further supports the American Academy of Pediatrics newly revised statement [60].…”
Section: Preventionsupporting
confidence: 77%
“…Interestingly enough, the lowest incidence at 1.7% was found in children whose mothers ate peanuts while breast-feeding and were introduced to peanuts before 12 months of age. If a mother did not do one of these actions, there was an increase in incidence of peanut sensitization [59]. This study further supports the American Academy of Pediatrics newly revised statement [60].…”
Section: Preventionsupporting
confidence: 77%
“…In the last 5 years, several studies have demonstrated allergen-specific oral tolerance induction to allergenic foods in highrisk children. [23][24][25][26][27] related allergic diseases, particularly food allergy. We present the experimental and human studies that have evaluated this approach and discuss various factors which may influence the success of these approaches, such as the type of emollient chosen for the intervention, the role of managing skin inflammation, and differences between primary and secondary prevention of atopic dermatitis to achieve the desired outcome.…”
Section: Pathog Ene S Is Of Food Allergymentioning
confidence: 99%
“…Likewise, a study called LEAP (Learning Early about Peanut Allergy) demonstrated that introducing a potential allergen (in this case: peanuts) at small doses into the diet early (at the age of 4–6 months) reduced the incidence of allergy to this allergen by 80% [ 63 ]. Recent studies confirmed that allergen introduction reduced peanut allergy incidence most effectively when peanuts were introduced into the mother’s diet during pregnancy and lactation and then into the infant’s diet [ 64 ]. Thus, dietary interventions during gestation and lactation period include a balanced diet without elimination of potential allergens ( Table 1 ).…”
Section: The Effect Of Nutritional Programming On Allergy Developmmentioning
confidence: 99%